Market efficiency in real time - Busse, Jeffrey A.; Clifton Green, T. (Journal of Financial Economics, 2002)
The Morning Call and Midday Call segments on CNBC TV provide a unique opportunity to study the efficient market hypothesis. The segments report analysts’ views about individual stocks and are broadcast when the market is open. We find that prices respond to reports within seconds of initial mention, with positive reports fully incorporated within one minute. Trading intensity doubles in the first minute, with a significant increase in buyer- (seller-) initiated trades after positive (negative) reports. Traders who execute within 15 seconds of the initial mention make small but significant profits by trading on positive reports during the Midday Call.